Lesbian, Gay, Biseksual dan Transgender (LGBT) dalam Perspektif Maqashid Syariah - Maulida, Afra Hikmatul; Saputra, Gusti Rian (Universitas Muhammadiyah Surabaya, 2024)
The phenomenon of lesbian, gay, bisexual and transgender (LGBT) still raises pros and cons among the public. The pro group of the idea takes refuge behind the principles of Human Rights (HAM). While the counter group tends to be normative and uses the basis of Islamic law in viewing LGBT issues. The two major currents of this group have never found common ground in positioning the LGBT issue. Therefore, through this research, researchers focus on maqashid sharia perspective which is considered to be the middle ground of the debate between the two groups. This research uses a normative approach and library research type. The main references in this research are various books on the theme of LGBT and maqashid sharia. The results show that according to the idea of maqashid sharia, LGBT as a lifestyle trend is not in line with the purpose of religion, namely the maintenance of offspring (hifdzul al-Nasl). This is because the impact of the LGBT culture of marrying and or having same-sex relationships cannot produce offspring naturally. In addition, the maintenance of offspring that aims to maintain the civilization of mankind is also contrary to the concept of LGBT. Keyword: LGBT, Maqashid syariah.